The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00590-020-02819-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dislocation after bipolar hemiarthroplasty: a retrospective case–control study of patients with CT data

Abstract: Purpose Bipolar hemiarthroplasty has been shown to have a lower rate of dislocation than total hip arthroplasty. However, as the influencing risk factors for bipolar hemiarthroplasty dislocation remain unclear, we aimed to analyse patient and surgeon-specific influencing risk factors for bipolar hemiarthroplasty dislocation. Methods We retrospectively analysed patients who were operated between 2012 and 2018 and had dislocated bipolar hemiarthroplasty and matched them to patients without a dislocated bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Nevertheless, despite the fact that a causative association of fracture morphology and posterior wall morphology in patients with traumatic posterior hip dislocation could not be determined in our study, we can state that a significant correlation of posterior wall morphology and fracture morphology can be made with a sensitivity of up to 88.9%. This is in line with our previous observations in patients with posterior bipolar hip arthroplasty dislocations [10].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, despite the fact that a causative association of fracture morphology and posterior wall morphology in patients with traumatic posterior hip dislocation could not be determined in our study, we can state that a significant correlation of posterior wall morphology and fracture morphology can be made with a sensitivity of up to 88.9%. This is in line with our previous observations in patients with posterior bipolar hip arthroplasty dislocations [10].…”
Section: Discussionsupporting
confidence: 94%
“…The method was adapted from Valera et al, who analyzed the acetabular shape and described the anterior and posterior acetabular coverage in healthy patients younger than 55 years without higher degrees of osteoarthritis [ 9 ]. Likewise, reduced posterior acetabular sector angle (PASA) and reduced posterior wall angle (PWA) were thought to be among the major patient-related specific factors influencing the risk for bipolar hemiarthroplasty dislocation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative pain, functional outcome, and differences in cost between the cohorts could also not be analyzed. Finally, dementia has been associated with an increased risk of re-interventions due to dislocation after hemiarthroplasty [25]. Re-interventions, however, were not captured in the current database and as such could not be reported.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Tsai et al analyzed 23 comorbidities and found that the only variables that predicted the need for revision surgery after THA for a hip fracture were end-stage renal disease, schizophrenia, and male sex 35 . Factors that have been identified as predictive of dislocation after hemiarthroplasty include surgical duration, dementia, surgical approach, and prosthesis-related factors 24,36,37 . We were unable to find evidence that the comorbidity burden or specific comorbidities other than dementia increased the risk of dislocation in this patient population.…”
Section: Discussionmentioning
confidence: 99%